Desempenho de uma biblioteca universitária baseada em indicadores de desempenho da ISO 11620: ações para melhoria do desempenho e da qualidade dos serviços prestados - Pimenta, Elaine Cristina Tomás (2016)
The use of indicators to evaluate the performance of library services has become increasingly necessary, and its results have helping to improve the functioning of services and management. This study aims to identify: what actions are needed to improve performance and quality of services provided by the Central Library Ufes. And aims to evaluate the Ufes Central Library using selected performance indicators of ISO 11620, and from the selection of the set of indicators identified in ISO 11620 in order to assess the performance of Ufes Central Library services apply the evaluation, analyze the results and propose improvement actions from the calculation of the results. The methodology is qualitative and quantitative. The first step of the methodology was based on a literature review; in the second step, the goal was to obtain a list of performance indicators indicators 35 which were selected to measure the performance of BC, and; the third stage, a field research was made which was used instruments: questionnaire form, observation and document analysis. For statistical analysis we used the Microsoft Office Excel software 2013. Research on the form with the participation of 135 users, and research with the questionnaire with the participation of 572 users. Result of some indicators: Titles Availability (87%), Number of academic publications owned by the institution in RI (12%), Number of affordable rare materials through the web catalog (40%), Hours open compared with demand (88%), Number of unused bonds (32%), Number of calls to users in training classes per individual (30), Cost per use of collection (R$ 32.81), The user service team as a percentage of the total staff (60%), etc. The necessary actions for solving the problems are: the realization of projects, placement of job production targets, training sessions for users, promotion of services, staff training, creating policies and increased funding for the purchase of materials. This search may be continued for the diagnosis performance of this library over the years.